KEANEKARAGAMAN JENIS TUMBUHAN PAKU-PAKUAN (PTERIDOPHYTA) PADA BERBAGAI UMUR LAHAN GAMBUT BEKAS KEBAKARAN DI DESA RASAU JAYA UMUM KABUPATEN KUBU RAYA - Kurniawati, Ella; Astiani, Dwi; M, Iskandar A (Universitas Tanjungpura, 2019)
The burning activity of peatlands in Kubu Raya Regency could kill various types of vegetation, one of which is ferns (Pteridophyta). Research on the species diversity of ferns needs to be execausted to obtain information or about the composition of the ferns species that present in peat ex-burn peat lands. This research was carried out at various ages sites (1, 2, 3 and 4 years) of ex-burn peat lands in Rasau Jaya Umum Village, Kubu Raya Regency. This study applyed survey metode with double plot technique, Plot laying using a purposive sampling methode, plot size was 5 x 5 m divided into 25 sub-plots of 1 x 1 m size.Three repetations were aplly made on each site. The results showed that on 1 year old ex-burn site were found 4 ferns species, paku ribu ribu (Lygodium microphyllum Cav.R.Br) paku cenceran (Neprolefis falcata Cap. C.Chr) paku lemiding (Stecchlanaena palustris Burm Bedd) andÂ paku resam (Gleichenia linearis Burn Clarke) and 2,3,4, years old ex-burn peatland 3 species of ferns were found, namely paku cenceran (Neprolefis falcata Cap. C.Chr) paku lemiding (Stecchlanaena palustris Burm Bedd) andÂ paku resam (Gleichenia linearis Burn Clarke). From the results of the study concluded that the diversity of species of ferns at various ages (1, 2, 3 and 4 years) of ex-burn peatlands in Rasau Jaya Umum Village, Kubu Raya Regency were not relatively similiar.Keywords: ex-burn peat land, fern, species diversity.